A Need Analysis to Identify Gaps in Teaching Writing Skills for English Teachers in Central Kalimantan - Elhawwa, Tazkiyatunnafs; Pionera, Mutiarani (Language Circle: Journal of Language and Literature, 2024)
The purpose of this research was to analyse the gaps in teaching writing skills for English teachers in Central Kalimantan. This research belonged to explore four main analyses: 1) Target need, 2) Present situations, 3) Learner factor, and 4) Mean. The subjects involved were the high school teachers who teach English in the Eastern, Western and Middle region of Central Kalimantan. Data needed in this mixed-method research was collected through observation, interview, and questionnaire. The result showed that English teachers in Central Kalimantan need to strengthen understanding about various teaching models and methods in helping to improve students' writing skills. In addition, they also need to optimally manage their teaching process. Since there were found that several teachers were reluctant to change their teaching style, they need further guidance and training to update their teaching approach. Last but not least, the teachers need to be continuously trained to adapt towards the development of technology nowadays.